Optimizing organizational agility through agile complexity tolerant leadership - Banuara Nadeak (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The main objective of this paper is to explore how the use of agile complexity can enhance organizational agility and competitive advantage in Small and Medium Enterprises (SMEs) during digital transformation. Additional objectives include addressing knowledge gaps in the leadership attributes needed to drive organizational agility, evaluating the research focus and methods used, and exploring agile complexity leadership as a model to enhance organizational performance. The research method involves a literature review using Google Scholar from 2013 to 2023, using keywords such as complexity, complexity science, leadership complexity, agile, and agile leadership. After initially identifying 81 journal articles, 13 relevant journal articles and four books were selected by reviewing their abstracts to assess their correlation with the role of agile complexity leadership in enhancing organizational agility during digital transformation in SMEs through prism model analysis. The main findings from this observation include a significant knowledge gap regarding the leadership attributes needed to enhance organizational agility, research dominance based on quantitative methods with statistically non-representative samples, and a lack of attention to the concept of complexity leadership as an effective model for improving SME performance. Although this paper provides new insights into the relationship between organizational agility and leadership during digital transformation in SMEs.